COMPARATIVE STUDY OF LONELINESS IN INDONESIAN AND MALAYSIAN STUDENTS - Vernanda Widya Pangestika; Sri Nugroho Jati; Vidyastuti n/a (State Islamic University (UIN) Ar-Raniry, 2024)
7.8% of teenagers in ASEAN including Indonesia and Malaysia reported mostly or always feeling lonely and 31.3% reported feeling lonely sometimes in the last 12 months. This is closely related to the similarities in demographic background and social and cultural background of these countries. This research aims to determine the comparative level of loneliness among students in Indonesia and Malaysia. Loneliness Statistics data states that 43% of young adults aged 17-25 years feel lonely. Initial research interviews showed that students experienced loneliness and felt several things such as not feeling close to people around them, often being abandoned and ostracized, fear of rejection, and so on. A total of 235 Indonesian and Malaysian students living in dormitories were involved in this research. The measurement instrument uses the loneliness scale. The collection technique uses purposive sampling. The research results show that there is no difference in loneliness between Indonesian and Malaysian students. Variable analysis found that the biggest factor causing loneliness in Indonesian students came from within themselves and in Malaysian students the biggest factor causing loneliness came from outside themselves.